Śrī Mācilāmaṇitēcikamūrttikal aruḷicceyta Tiruñāṉacampantar piḷḷaittamiḻ - Mācilāmaṇitēcikamūrtti (SAMP early 20th-century Indian books project ;, 1953)
Poems in piḷḷaittamiḻ, a Tamil minor literary form, in praise of Campantar, 7th century Tamil Śaivite poet.